New approaches to social problems treatment - Burns, Stacy Lee.; Peyrot, Mark. (Bingley, UK : Emerald, 2010)
This volume examines diverse developments in the evolution of public policy institutions for remedying social problems. The collected chapters address the transformation of social problems, social problems work, and social problems solutions in the context of criminal justice, mental health, and community institutions (schools) in contemporary society. These diverse settings and institutions collectively reflect a trend toward the use of various 'treatment' initiatives within formal disciplinary systems and as part of legalistic social control strategies. Although all of the remedial approaches considered are 'new' in the sense of being recent innovations, many are only the most recent in a long sequence of policy initiatives. The contributors to the collection demonstrate that recent transformations in remedial approaches to social problems and the challenges faced by such policy initiatives are as much a function of what has come before as they are of their own inherent features.
Part I: Introduction. New approaches to social problems remedies / Stacy Lee Burns and Mark Peyrot -- Part II: New Forms of Deviance. Hate crimes and their criminalization / Tim J. Berard -- Part III: Sexual Offenses : creating victim-centered criminal justice practices for rape prosecution / Amanda Konradi ; Forgotten victims, unforgiven perpetrators : social problems work with adult male sexual offenders who purport to have been sexually victimized as children / Michael Petrunik and Adina Ilea -- Part III: Violence and Schools. The columbine effect and school anti-violence policy / Glenn W. Muschert and Anthony A. Peguero ; The gang's school : challenges of reintegrative social control / Robert Garot -- Part V: Substance Abuse in the Courts. Losing hope : the production of failure in drug court / Mitchell B. Mackinem and Paul Higgins ; Standardizing social problems solutions : the case of court-supervised drug treatment / Stacy L. Burns and Mark Peyrot -- Part VI: Correctional Treatment. Recovery and punishment : reconciling the conflicting objectives of coercive treatment in correctional settings / Holly Ventura Miller, J. Mitchell Miller, Rob Tillyer and Kristina M. Lopez ; Ex-inmates with psychiatric disabilities returning to the community from correctional custody : the forensic transition team approach after a decade / Stephanie Hartwell -- Part VII: Conclusion. Social problems and public policy : a theoretical overview of policy issues and implications / Mark Peyrot and Stacy Lee Burns.
Description based on print version record.
Keywords: Social problems -- United States; Social issues & processes; Social welfare & social services; Social Science -- Human Services; Political Science -- Public Policy -- Social Policy; United States -- Social policy